PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS PUISI SISWA KELAS VIII SMP NEGERI 31 PADANG - Ena Noveria, Reno Mardhatillah Sari, Ermawati Arief, (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The purpose of this study is (1) to determine the level of skill of writing poetry text of grade VIII of SMP Negeri 31 Padang before using  problem based learning model with audiovisual media. (2) to determine the level of  writing’s skill on poetry text of  grade VIII  of  SMP Negeri 31 Padang after using  problem based learning model with audiovisual media. (3) analyze the effect application problem based learning model with audiovisual media assisted to the skill of writing poetry text in grade VIII students of SMP Negeri 31 Padang. This type of research is quantitative experimental method. Based on data analysis, using  problem based learning  model  with audiovisual media toward students writing’s skill on poetry text in grade VIII students of SMP Negeri 31 Padang. Kata kunci: pengaruh,  model problem based learning, media audio visual,        teks puisi